Leading With Questions
Based upon interviews with scores of leaders who lead with questions, this book presents the power of asking the questions that lead to real solutions and answers in today\\\'s complicated world of business. Leading with Questions provides a comprehensive foundation for effectively employing questions when leading others. It offers a variety of principles and strategies for asking questions and stories illustrating how leaders from every type of organization have used questions to attain organizational success and personal fulfillment. When, how, why, and where to lead with questions are described and exemplified.